Revealing Subtitling Strategies in the Translation of Wednesday Episode 1 - Ahmad Jum'a Khatib Nur Ali; Ichwan Suyudi; Agung Prasetyo Wibowo (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
The commissive speech acts help manage situations where linguistics form does not fully reflect the intended meaning. Consequently, translating commissive speech acts in films requires particular care and consideration. Therefore, this research objective is to analyse the application of subtitling strategies in the translation of commissive speech act dialogues in the series Wednesday Episode 1, based on Gottlieb?s (1992) theoretical framework. Subtitling, as a form of audio-visual translation, requires linguistic and technical adjustments so that messages can be conveyed accurately within the constraints of space and time. This study employs a descriptive qualitative method with documentation techniques as the basis for data collection. A total of seven data items were obtained, consisting of utterances taken from the source script and their translations. The findings reveal that several subtitling strategies were used: paraphrase (2 data), transfer (1 datum), imitation (2 data), decimation (1 datum), and deletion (1 datum). Paraphrase strategy was the most frequently used strategy due to its flexibility in handling expressions without direct Indonesian equivalents. Transfer strategy was applied when meanings could be conveyed directly, while imitation strategy used for proper and place names. Decimation and deletion strategies used to address technical constraints like rapid dialogue and limited subtitle space. Overall, this study concludes that subtitling strategies are chosen contextually to maintain the accuracy, naturalness, and readability of subtitles for the audience.